2018
DOI: 10.5194/acp-18-11277-2018
|View full text |Cite
|
Sign up to set email alerts
|

No robust evidence of future changes in major stratospheric sudden warmings: a multi-model assessment from CCMI

Abstract: Abstract. Major mid-winter stratospheric sudden warmings (SSWs) are the largest instance of wintertime variability in the Arctic stratosphere. Because SSWs are able to cause significant surface weather anomalies on intra-seasonal timescales, several previous studies have focused on their potential future change, as might be induced by anthropogenic forcings. However, a wide range of results have been reported, from a future increase in the frequency of SSWs to an actual decrease. Several factors might explain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
8
33
0
Order By: Relevance
“…Figure 1a shows the average frequency of SSWs during the period 1958-2014 in JRA-55 reanalysis (horizontal dashed line) and the corresponding value for the CMIP6 models (bars; the numerical values are given in supporting information Table S1). In agreement with prior studies (e.g., Ayarzagüena et al, 2018;Charlton-Pérez et al, 2013), we find a large spread across the models in the mean frequency of SSW over that period. This spread is likely due, in part, to the large internal variability of the polar wintertime stratosphere; even with an identical climate model, the frequency of SSWs can vary greatly across different realizations, as demonstrated by Polvani et al (2017).…”
Section: Model Simulation Of Ssws During the Historical Period: Mean supporting
confidence: 92%
See 2 more Smart Citations
“…Figure 1a shows the average frequency of SSWs during the period 1958-2014 in JRA-55 reanalysis (horizontal dashed line) and the corresponding value for the CMIP6 models (bars; the numerical values are given in supporting information Table S1). In agreement with prior studies (e.g., Ayarzagüena et al, 2018;Charlton-Pérez et al, 2013), we find a large spread across the models in the mean frequency of SSW over that period. This spread is likely due, in part, to the large internal variability of the polar wintertime stratosphere; even with an identical climate model, the frequency of SSWs can vary greatly across different realizations, as demonstrated by Polvani et al (2017).…”
Section: Model Simulation Of Ssws During the Historical Period: Mean supporting
confidence: 92%
“…We also note that the lack of consensus in the CMIP6 models agrees with the recent study of Ayarzagüena et al (2018), who analyzed the chemistry climate model projections of the CCMI models, which were forced with RCP6.0 scenario. While reporting a general tendency toward an increased frequency of SSWs by the end of the current century, they also emphasized that most changes were not statistically significant.…”
Section: Future Changes In Sswssupporting
confidence: 89%
See 1 more Smart Citation
“…4c and d. Specifically, ozone anomalies are usually accompanied by anomalies in the Arctic vortex ( Fig. 4a and b), and previous work has shown that spring Arctic vortex anomalies independent of ozone can influence surface conditions (Black and McDaniel, 2007;Ayarzagüena and Serrano, 2009;Hardiman et al, 2011). We now demonstrate that vortex anomalies are associated with polar cap PS anomalies in the CCMI models as well and then try to isolate statistically the relative importance of ASO.…”
Section: Effect Of Arctic Stratospheric Ozone (Aso) On Polar Surface supporting
confidence: 64%
“…The stratospheric polar vortex is also expected to change in the future as a result of long-term anthropogenic changes in atmospheric composition, that is, increasing greenhouse gas (GHG) concentrations and stratospheric ozone layer recovery. For instance, several studies have examined possible trends in the future occurrence of midwinter SSWs (e.g., Ayarzagüena et al, 2018;Bell et al, 2010;Hansen et al, 2014;Karpechko & Manzini, 2017;Kim et al, 2017;Manzini et al, 2014;Mitchell et al, 2012;SPARC CCMVal, 2010), but no consensus has been reached yet. Nevertheless, the effects of projected climate change on SFWs have not been addressed.…”
Section: Introductionmentioning
confidence: 99%